A design of selective solar absorber for high temperature applications - Al-Rjoub, A. (2018)
This study presents a design of multilayer solar selective absorber for high temperature applications. The optical stack of this absorber is composed of four layers deposited by magnetron sputtering on stainless steel substrates. The first is a back-reflector tungsten layer, which is followed by two absorption layers based on CrAlSiNx/ CrAlSiOyNx structure for phase interference. The final layer is an antireflection layer of SiAlOx. The design was theoretically modelled with SCOUT software using transmittance and reflectance curves of individual thin layers, which were deposited on glass substrates. The final design shows simultaneously high solar absorbance = 95.2 % and low emissivity ε= 9.8% (at 400 ºC) together with high thermal stability at 400 ºC, in air, and 600 ºC in vacuum for 650 h.